2019
DOI: 10.1021/acs.joc.8b02940
|View full text |Cite
|
Sign up to set email alerts
|

A pH-Switchable Electrostatic Catalyst for the Diels–Alder Reaction: Progress toward Synthetically Viable Electrostatic Catalysis

Abstract: Density functional theory calculations at the SMD/M06-2X/6-31+G­(d,p)//M06-2X/6-31G­(d) level of theory have been used to computationally design and test a pH-switchable electrostatic organocatalyst for Diels–Alder reactions. The successful catalyst design, bis­(3-(3-phenylureido)­benzyl)­ammonium, was studied for the reaction of p-quinone with range of cyclic, heterocyclic, and acyclc dienes and also the reaction of cyclopentadiene with maleimide and N-phenylmaleimide. All reactions showed significant enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 32 publications
(45 reference statements)
1
43
0
4
Order By: Relevance
“…Significantly, we find that the magnitude and sign of the switches presented in Figure 2 are more strongly linearly correlated with the change in barrier to (E)-(Z) isomerization (R 2 =0.64) than with the corresponding change in barrier to cycloaddition (R 2 =0.32; Appendix S6). After consideration, this is not surprising; we 20,21 and others 31 have previously demonstrated that electrostatic catalysis of the Diels-Alder reaction depends strongly upon the relative orientation of the applied field with respect to the bond-forming axis from the incoming dienophile (the "reaction-axis rule"), 1,11 which in this case is orthogonal to the plane of the ring system to which the CFG is attached and therefore unlikely to have any catalytic effect (Scheme 3B).…”
Section: Diels-alder Versus Isomerizationmentioning
confidence: 90%
“…Significantly, we find that the magnitude and sign of the switches presented in Figure 2 are more strongly linearly correlated with the change in barrier to (E)-(Z) isomerization (R 2 =0.64) than with the corresponding change in barrier to cycloaddition (R 2 =0.32; Appendix S6). After consideration, this is not surprising; we 20,21 and others 31 have previously demonstrated that electrostatic catalysis of the Diels-Alder reaction depends strongly upon the relative orientation of the applied field with respect to the bond-forming axis from the incoming dienophile (the "reaction-axis rule"), 1,11 which in this case is orthogonal to the plane of the ring system to which the CFG is attached and therefore unlikely to have any catalytic effect (Scheme 3B).…”
Section: Diels-alder Versus Isomerizationmentioning
confidence: 90%
“…In this regard, Coote and coworkers 12,13 focused mainly on pH-switchable D-LEFs and demonstrated among others that bond-dissociation energies (BDEs) can be effectively tuned with the help of the electrostatic field resulting from protonation/deprotonation of a distant (though sufficiently close) acidic/basic group. Furthermore, the same authors recently explored the use of pH-switchable D-LEFs as a strategy for selectively modifying photochemical reactivity, 28 catalyzing Diels-Alder reactivity, 29 and inducing mechanistic crossover in nucleophilic substitution reactions from S N 1 to S N 2. 30 Others have probed the role played by electrostatics in metal-based catalysts and the effect of ligand coordination on their catalytic activity.…”
Section: Designed Local Electric Fieldsmentioning
confidence: 99%
“…12 While these experiments are difficult to scale for chemical synthesis, we have shown that the electric fields from remote charged functional groups, embedded on the substrate or a catalyst, can be used to catalyse chemical reactions and alter their outcome. [13][14][15][16][17][18][19][20][21][22][23][24][25] The charged group can be a Lewis acid, or an acid or base, whose charge and hence electric field, can be altered with pH. While again much of the work to date has been computational, experiments have validated these predictions in a growing number of systems.…”
Section: Introductionmentioning
confidence: 99%